ANALISIS KEBUTUHAN BAHAN AJAR DIGITAL PADA MATA PELAJARAN IPAS DI SD NEGERI 141 PALEMBANG - Puspitasari, Oktaria; Sholeh, Kabib; Lara Syaflin, Sylvia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the rapid development of digital technology and its potential use in improving the quality of education. This study aims to analyze the need for digital teaching materials in the subject of science and natural sciences at SD Negeri 141 Palembang. This study focused on grade IV elementary school students as research subjects, using a descriptive qualitative approach. To obtain research data, researchers used data collection techniques, namely observation, questionnaires, interviews and documentation. Data analysis was carried out using data reduction, data presentation, and conclusions. Based on the data, it shows that the use of digital teaching materials in the subject of science and natural sciences at SD Negeri 141 Palembang is still low. It can be seen from the results of the questionnaire which showed an average score of 53% with low criteria, where the results of the questionnaire showed 26 students chose to strongly agree with a percentage of 92.86% and 2 other students chose moderate with a percentage of 7.14%.